Studi Pelepasan Beban Pada PLTU Keramasan Saat Terjadi Penurunan Frekuensi - lingga, Melingga; Azis, Abdul; Pebrianti, Irine Kartika (Universitas Semarang, 2021)
The demand for electric power increases along with the development of technological progress and development. The use of electricity is an important factor in people's lives, both in households, lighting, communication, and industrial. The purpose of this research is to calculate the frequency response before load shedding, to calculate the frequency response after load shedding and to analyze the load recovery after normal frequency in the load. The methods to be used in writing and discussing this research are: Observation Method, Interview Method / Interview, Literature Study Method. Based on the calculation of the data in the previous chapter, the following conclusions can be drawn, the calculation of the conditions before carrying out the load shedding is based on the rate of decreasing frequency from the result obtained is 1.6 Hz / s, then to calculate the time used in determining the frequency at the time of load shedding then the results obtained are 54 Hz, Meanwhile, to calculate the frequency after load shedding that is obtained is 49.1 Hz, Calculation of load shedding time is expected when there is a decrease in frequency of 10.5 seconds, Calculation of the load rate of increase expected after load shedding then the optimal load value that must be removed is 5.55 w.